Taking care of the parents and the baby to rescue the affective bound: a study based on Joyce Travelbee - Rolim, Karla Maria Carneiro; Bezerra, Maria Gorette Andrade; Moreira, Vládia Teles; Araújo, Thelma Leite de (Rev Rene, 2003)
A study was made during the year of 2002, on how to minimize the conflicts of experiences among professionals involved with public health, in particular in relation to nurses. We objective was the particular situation of a family whose mother and don were patients on separated units of a large hospital in Fortaleza-Ceará, and the father was at home. We looked at how to rescue the affective bound and how to establish the relation nurse/family. We concluded that it is of great importance for the nurse to base his or her behavior on the scientific method, following the Theory of Personal Relationship of Travelbee. We confirmed the major importance of human being in our technological world.